Invasive Trichosporon Infection: a Systematic Review on a Re-emerging Fungal Pathogen - de Almeida Júnior, João N.; Hennequin, Christophe (Frontiers in Microbiology, 2016)
Objectives: This review aimed to better depict the clinical features and address the issue of therapeutic management of Trichosporon deep-seated infections. Methods: We comprehensively reviewed the cases of invasive Trichosporon infection reported in the literature from 1994 (date of taxonomic modification) to 2015. Data from antifungal susceptibility testing (AST) studies were also analyzed. Results: Two hundred and three cases were retained and split into four groups: hemopathy (n=79), other immunodeficiency conditions (n =41), miscellaneous (n=58) and newborns (n=25). Trichosporon asahii was the main causative species (46.7%) and may exhibit cross-resistance to different antifungal classes. The unfavorable outcome rate was at 44.3%. By multivariate analysis, breakthrough infection (OR 2.45) was associated with unfavorable outcome, whilst the use of an azole-based therapy improved the prognosis (OR 0.16). Voriconazole-based treatment was associated with favorable outcome in hematological patients (73.6% vs. 41.8%; p=0.016). Compiled data from AST demonstrated that (i) T. asahii exhibits the highest MICs to amphotericin B and (ii) voriconazole has the best in vitro efficacy against clinical isolates of Trichosporon spp. Conclusions: Trichosporon infection is not only restricted to hematological patients. Analysis of compiled data from AST and clinical outcome support the use of voriconazole as first line therapy.